Pemanfaatan Teknologi Near Field Communication untuk Penyampaian Informasi Multimedia di Museum Negeri Mpu Tantular - Ryan Christian Wiguno; Henry Novianus Palit; Djoni Haryadi Setiabudi (Jurnal Infra, 2015)
Museum is a place to store a variety of cultural heritage that can be used as an educational attraction for the community and study materials used by academics. But unfortunately the public interest to make the museum as a tourist destination is very low. Therefore we need innovation to attract people, and in this case the innovation made in the utilization of NFC technology in android . NFC technology is currently being highly developed and has been used in many applications, so the utilization of that technology is expected to dispel the impression of being outdated and unattractive, commonly attached to the museum.This application will be divided into two, namely mobile applications for visitors that have been developed using Android Studio software and web applications for administrator that developed using Notepad++ and MySQL database. This mobile applications can deliver information of objects in the museum in the form of text, video, and audio by scanning the NFC tag which the results of the scan will direct the application to retrieve data from a web application as a server for database management. This application can also display museum’s profile, museum’s events, museum’s maps, and mini games. From this application museum can also obtain statistical data which can be useful for the development of the museum that can be accessed from web application.Based on the results of implementation which has been tested, this application was able to deliver the information in the format of text, image, audio, and video by scanning NFC tag. In addition, from the application feasibility tests on random users, all respondents express that they are more interested to visit museum with the presence of this application.